El rol de China en la economía asiática e implicancias para la economía mundial - Aquino Rodríguez, Carlos (2013)
China is a key actor in the Asian economy. It is the biggest market for them, the factory of Asia and the world, where parts and components produced by them are assembled in China and exported to the world. It concentrate most of investment of several Asian countries, China also is changing the engine of its economy from exports and investment to consumption. The appreciation of its currency, the Yuan, helps in this direction. It is expected that China will become one of the engines, the main one, of the world economy. In fact, it is already for many countries, like to Peru.